1998
DOI: 10.1055/s-0037-1615064
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Detection of Activated Factor IX: Application to the Analysis of Different Therapeutical Factor IX Concentrates and Prothrombin Complexes

Abstract: SummaryA very sensitive and highly reliable test system for the detection of activated coagulation factor IX (FIXa) has been established. This assay system is based on the cleavage of a fluorogenic substrate by activated factor X (FXa) which is generated by FIXa. This assay can be used to process a large number of samples at a time and, being based on the convenient microtiter plate format, can easily be adapted to automated processing for routine screening of large sample numbers.With this assay at hand we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Thromboembolic complications after PCC administration were reported repeatedlyinseveral cases (5)(6)(7). The causeofthe thrombogenicity of PCCcould not be conclusively demonstrated to date,but it waswidely accepted thatactivated factor IX (FIXa) caused suchc omplications (8)(9)(10)(11).H owever, we could demonstratethat it is highlyunlikelythat FIXa is the causative agent (12). Instead, using amodel of in vitro "normalization" of coumarinp lasma,w eh ypothesizedt hat by dosing PCCa ccording to FIX content the concomitant prothrombin supplement caused thromboembolic complications (13).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Thromboembolic complications after PCC administration were reported repeatedlyinseveral cases (5)(6)(7). The causeofthe thrombogenicity of PCCcould not be conclusively demonstrated to date,but it waswidely accepted thatactivated factor IX (FIXa) caused suchc omplications (8)(9)(10)(11).H owever, we could demonstratethat it is highlyunlikelythat FIXa is the causative agent (12). Instead, using amodel of in vitro "normalization" of coumarinp lasma,w eh ypothesizedt hat by dosing PCCa ccording to FIX content the concomitant prothrombin supplement caused thromboembolic complications (13).…”
mentioning
confidence: 95%
“…Thethrombin generation assaywas performed as described (13).FIXa wasdeterminedasdescribed (12).FIXa titration was carried outaspreviouslydescribed by Lentingetal. (18)with Pe-fafluorI Xa (Pentapharm, Basel, Switzerland)a ss ubstrate and WHOA T( WHO-NIBSC 96/5 20) as inhibitor.T he in vivo thrombogenicity test (inN ew Zealand white rabbits) wasp erformeda ccording to (16), employing purifiedp roteinsi nc oncentrations as observedinthe PCCwith thromboembolic complications in its history.…”
mentioning
confidence: 99%
“…A reduction in thromboembolic complications among haemophilia B patients was observed when highly-purified factor IX began to replace PCCs. However, direct measurement of activated factor IX revealed that there tended to be higher levels in highly-purified factor IX preparations than in PCCs [28], suggesting that levels of activated factor IX do not correlate with thrombogenicity.…”
Section: Pccs and Thrombotic Risk: Pathogenesismentioning
confidence: 99%
“…Coagulant active phospholipids, which have been detected in PCCs, were also discussed as potent thrombogenic triggers potentiating the effect of activated coagulation factors [49]. During the last few years, scientific data were accumulating which showed without a doubt that prothrombin overload is causing thromboembolic complications while treating patients with PCCs [50][51][52].…”
Section: Thrombogenicitymentioning
confidence: 99%